2018
DOI: 10.2134/agronj2018.01.0023
|View full text |Cite
|
Sign up to set email alerts
|

Do Tillage, Cover Crops, and Compost Management within Organic Grain Cropping Affect Greenhouse Gas Emissions?

Abstract: Core Ideas Drought decreased the CO2 and N2O 2 out of 3 yr of the study but in a normal precipitation year, GHG emissions increased significantly for corn and wheat but stayed relatively low for soybean. Increasing compost from 1× to 1.5× the recommended rate showed no increase in N2O emissions. NTCC and 1×+ compost rates typically resulted in the greatest GWP. Organic crop production is increasing with consumer demand, but research is needed on the best management practices that minimize greenhouse gas (GHG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Compost is more beneficial than inorganic fertilizers from a sustainable agriculture perspective [11,13] because chemical fertilizers can have negative impacts on the environment [14]. However, the practice of using compost based on the N content may create an imbalance in plant nutrient availability [10,15]. Compost also contains organically bound N, phosphorus (P), potassium (K), calcium (Ca), and micronutrients, which support crop production through their effects on various physical and chemical processes in the soil [7,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compost is more beneficial than inorganic fertilizers from a sustainable agriculture perspective [11,13] because chemical fertilizers can have negative impacts on the environment [14]. However, the practice of using compost based on the N content may create an imbalance in plant nutrient availability [10,15]. Compost also contains organically bound N, phosphorus (P), potassium (K), calcium (Ca), and micronutrients, which support crop production through their effects on various physical and chemical processes in the soil [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of compost application varies from farmer to farmer, but in general, the rate is determined with its N content [7], which depends upon the feed type, bedding materials, confinement time, and the duration of composting [11]. The high rate of compost application often supports crop production by improving soil health and nutrient availability [15], but it can lead to salt accumulation and negatively affect root growth and biomass production. High salt concentration in soils decreases microbial population, affects soil structure, organic matter mineralization, and nutrient availability [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…yield and quality, is getting increasingly popular (Boardman et al, 2018). Organic farming can provide ecosystem services similar to or better than conventional farming where chemical fertilizers, herbicides, and pesticides are used for crop production (Cavigelli et al, 2013).…”
mentioning
confidence: 99%
“…Organic crop production can emit greenhouse gas (GHG) differently than conventional crop production. Boardman et al (2018) found that increased rate of compost application in organic farming increased N 2 O emissions. Hurisso et al (2016) reported that CO 2 and N 2 O emissions were lower in the organic than the conventional farming system under winter wheat (Triticum aestivum L.), but emissions were greater in the conventional than the organic system under fallow.…”
mentioning
confidence: 99%